Click-tambjamines as efficient and tunable bioactive anion transporters. Issue 21 (19th February 2020) - Carreira-Barral, Israel; Mielczarek, Marcin; Alonso-Carrillo, Daniel; Capurro, Valeria; Soto-Cerrato, Vanessa; Pérez Tomás, Ricardo; Caci, Emanuela; García-Valverde, María; Quesada, Roberto
Abstract : A novel class of transmembrane anion carriers, the click-tambjamines, display remarkable anionophoric activities in model liposomes and living cells. Abstract : A novel class of transmembrane anion carriers, the click-tambjamines, display remarkable anionophoric activities in model liposomes and living cells. The versatility of this building block for the generation of molecular diversity offers promise to develop future drugs based on this design.